1979
DOI: 10.1002/cne.901850102
|View full text |Cite
|
Sign up to set email alerts
|

Axonal guidance during embryogenesis and regeneration in the spinal cord of the newt: The blueprint hypothesis of neuronal pathway patterning

Abstract: In our previous studies on studies on spinal cord regeneration in the adult lizard and the newt, we observed that the radial processes of the regenerating ependyma form between them channels which are subsequently invaded by growing neurites. In the present study we compare embryogenesis of the newt spinal cord with regeneration in the adult. Except for minor differences, we observed that the germinal neuroepithelium of the embryo and larva patterns the longitudinal neural tracts in a similar manner. With thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
168
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(181 citation statements)
references
References 21 publications
12
168
1
Order By: Relevance
“…Sealing of ependyma during spinal cord regeneration was also confirmed in other regeneration-competent species in both adult and larval stages , Chernoff et al, 2003. It is thought to be a common process both in tail amputation and spinal cord transection in urodeles (Butler and Ward, 1967;Singer et al, 1979;Stensaas, 1983). In the case of zebrafish, even crush injury, which involves ependymal disruption, can cause ependymal sealing and formation of the ependymal bulb.…”
Section: Ependymal Sealing Is a Regenerative Response An Important Cmentioning
confidence: 77%
“…Sealing of ependyma during spinal cord regeneration was also confirmed in other regeneration-competent species in both adult and larval stages , Chernoff et al, 2003. It is thought to be a common process both in tail amputation and spinal cord transection in urodeles (Butler and Ward, 1967;Singer et al, 1979;Stensaas, 1983). In the case of zebrafish, even crush injury, which involves ependymal disruption, can cause ependymal sealing and formation of the ependymal bulb.…”
Section: Ependymal Sealing Is a Regenerative Response An Important Cmentioning
confidence: 77%
“…When examined in vivo, some of the very first axons growing out into the CNS and PNS extend through spaces formed between other cells. In the mid-1970s Marcus Singer and colleagues championed the idea that these physical channels-interstitial spaces created by clearings amongst radial processes of the ependyma and germinal neuroepithlium-serve as a "blueprint" for axonal growth (Singer et al 1979). By electron microscopy, the spaces seem to be filled with "light amorphic material" (Nordlander and Singer 1982).…”
Section: Substrata In Vivomentioning
confidence: 99%
“…Previous studies have shown that following spinal cord transection the ependymal cells seal over the cut ends of the spinal cord, form an ependymal bulb, and migrate into the lesion site from the cranial and caudal wound stumps (Stensaas, 1983). Morphological examination (Stensaas, 1983;Singer et al, 1979) has shown the cellular composition of the lesion site initially consists solely of ependymal cells and their progeny. Blood vessels are not found within the regenerating region of the cord itself, but are found in the meningeal layer surrounding the spinal cord.…”
Section: Ependymal Outgrowth In Vivomentioning
confidence: 99%
“…In animals that undergo successful spinal cord regeneration throughout life, the spinal cord is stimulated by injury to enter a period of rapid growth and tissue remodeling (Anderson et al, 1986;Egar and Singer, 1972;Simpson, 1968). During the remodeling process, reactive ependymal cells proliferate, migrate into the lesion site, and modify the intercellular environment into which regenerating axons grow (Piatt, 1955;Singer et al, 1979). In mammals, the predominant injury-reactive glial population is the astrocyte (Liuzzi and Lasek, 1987;Reier and Houle 1988), which produces a "glial scar" and inhibits regeneration (Reier, 1986;Fawcett et al, 1989).…”
mentioning
confidence: 99%